Effect of Friction Stir Welding on the Mechanical and Microstructural Behaviour of AA7075 Aluminium Alloy. (10th September 2022) - Mahesha, C. R.; Suprabha, R.; Kumar, Nellore Manoj; Kosanam, Koushik; Anandaram, Harishchander; Ramana Murty Naidu, S. C. V.; Kalyan Chakravarthi, M.; Govindarajan, Venkatesan
Abstract : In this research work, an attempt was made to weld AA7075 alloy using the friction stir welding (FSW) technique. The experimental runs were designed using the Taguchi L18 orthogonal array and welds were obtained by varying tilt angle, tool rotation speed, tool feed rate, and axial load, whereas weld quality was accessed in terms of tensile strength and microhardness. The microstructure was examined using an optical microscope. The studies revealed that the tool angle was the most influential factor followed by the tool feed rate as both the parameters impacted the intensity of heat developed. It was observed that the tool tilt decreased the microhardness of the welds. The UTS values and macrostructure imply that the weld should be subjected to higher tool torque conditions. The material flow was not periodic nor coordinated, as seen by the tool-tilted weld's macrostructure. With a tool tilt, the weld pressure is lowered, and the lower pressure could not be enough to prevent volumetric defects. The reduced pressure at quicker welding rates may have had an effect on the development of flaws.